Embedded Firmware Solutions : Development Best Practices for the Internet of Things - Sun, Jiming; Jones, Marc; Reinauer, Stefan; Zimmer, Vincent (Springer Nature, 2015)
Computer science
English
Keywords: Computer science; Computer science